Central Bank Interventions, Communication and Interest Rate Policy in Emerging European Economies - Balázs Égert (Oesterreichische Nationalbank (OeNB), 2006)
This paper analyses the effectiveness of foreign exchange interventions in Croatia, the Czech Republic, Hungary, Romania, Slovakia and Turkey using the event study approach. Interventions are found to be effective only in the short run when they ease appreciation pressures. Central bank communication and interest rate steps considerably enhance their effectiveness. The observed effect of interventions on the exchange rate corresponds to the declared objectives of the central banks of Croatia, the Czech Republic, Hungary and perhaps also Romania, whereas this is only partially true for Slovakia and Turkey. Finally, interventions are mostly sterilized in all countries except Croatia. Interventions are not much more effective in Croatia than in the other countries studied. This suggests that unsterilized interventions do not automatically influence the exchange rate.
Keywords: F31; 330; central bank intervention; communication; foreign exchange intervention; verbal intervention